(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: To explore the various perceived causes and solutions for substance abuse among the nursing students in Mangalore, Karnataka, India. Methods: Group of nursing students belonging to the second year participated in the study. A method of free listing and pile sorting was employed to discover the causes and solutions for substance abuse. Conclusion: The primary cause of substance abuse was found to be peer pressure with a salience value of (0.945) followed by enjoyment (0.614), family problems (0.486). Cognitive mapping revealed the causes of being grouped under three major headings: psychological imbalance, adaptation to modern lifestyle, and unhealthy family environment. The solutions suggested by the students were counseling and rehabilitation with the highest salience value (0.751), awareness about the adverse effects at an early age (0.637). Cognitive mapping portrayed the solutions grouped into headings like therapies and treatment, external sources, family care, and support. Factors such as peer pressure, academic pressure, and easy availability of drugs can be looked into by external institutions to root out the evils of substance abuse